Effects of iron, aluminium, dissolved humic material and acidity on grayling (Thymallus thymallus) in laboratory exposures, and a comparison of sensitivity with brown trout (Salmo trutta) - Vuorinen, Pekka J.; Keinänen, Marja; Peuranen, Seppo; Tigerstedt, Christina
Iron alone, as well as aluminium, can be acutely lethal in humus-free acidic water. In a simultaneous laboratory exposure to both Fe and Al the toxic effects on grayling were even more pronounced. Water acidity increased and dissolved humic material reduced the toxicity of Fe and Al. As toxic effects, the ionoregulation of yolk-sac fry was disturbed, swimming activity decreased and mortality increased. Based on mortality and swimming activity, brown trout yolk-sac fry tolerated, depending on the Al concentration, nearly half a pH unit more of acidity than those of grayling. The gills of the affected one-summer-old grayling were damaged, leading to decreased oxygen uptake and disturbed ionoregulation. In cold water (3 °C), one-summer-old grayling did not recover completely from the sublethal exposure. Some tributary waters of Isojoki, a river in West-Central Finland, were toxic to grayling yolk-sac fry. These waters had rather high Al and Fe concentrations but were humic and only slightly acidic. It is concluded that increased concentrations of Fe and Al increases the harmfulness of waters in forestry land use or peat production areas even in humic and slightly acidic waters.